Nivel de satisfacción de los usuarios en relación al rol bioético de enfermería, área de emergencia del Hospital General IESS Babahoyo, octubre 2024 – mayo 2025. - Gamarra Vásquez, Mel Stefany (2025)
This study aims to examine the level of user satisfaction regarding the bioethical role played by nursing staff in the emergency area of the IESS Babahoyo General Hospital, in the period between October 2024 and May 2025. The main purpose is to establish how the implementation of bioethical principles (autonomy, beneficence, equity and respect for human dignity) influences patients' perception of the quality of care received. The methodology is based on a quantitative and descriptive approach, using structured surveys administered to a representative sample of 74 patients. Data processing was carried out with statistical tools such as SPSS and Minitab, in order to identify patterns and relationships between the variables analyzed. The results of the study revealed a balanced distribution between genders, with 45.9% of respondents perceiving full availability of equipment, and 39.2% experiencing a waiting time of more than 30 minutes to receive care. In addition, 41.9% considered the staff to be professional, while 32.4% reported problems related to care. The Cronbach's alpha analysis yielded a value of 0.788, indicating acceptable reliability in the scale used, ensuring the internal consistency of the items evaluated. In conclusion, user satisfaction in the emergency department of the IESS Babahoyo Hospital is positive, highlighting the respectful care and ethics of the nursing staff, although problems related to the availability and speed of care persist.